PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG HAK REPRODUKSI KELAS XII DI SMA NEGERI 18 BATAM - Lusianti, Lusianti; Utami, Risqi; Sulistyawati, Tri Ribut (Universitas Batam, 2021)
The 1945 Constitution mandates to protect and guarantee the rights of every child. However, until now the protection of children has not fully run optimally, marked by the presence of children who experience sexual violence. Based on the data, there were 119 cases of sexual violence against children in Riau Islands in 2017. The purpose of the study was to determine the effect of health education on the knowledge and attitudes of young women about reproductive rights. Pre-experimental research design with one group pretest-posttest. Held in December-January at SMA Negeri 18 Batam. The total population is 142 people and the number of samples using purposive sampling technique is 105 respondents. And a questionnaire measuring instrument (pretest-posttest). Data analysis used statistical test dependent sample T-test. The results of the analysis that the average knowledge before health education is 8.83 and after 15.29, so that there is an increase of -6.46, p-value 0.000 (p 0.05) thus the hypothesis is Ha. The mean attitude before health education was 35.16 and after 68.37 there was an increase of -33.21, p-value 0.000 (p 0.05) so the hypothesis is Ha. From the results of the analysis, it was found that there were significant differences and the effect of health education on the knowledge and attitudes of young women about reproductive rights. Suggestions for teenagers to be more active in seeking information about reproductive rights, in order to have good knowledge to prevent risks that may occur so that they can be prevented as early as possible